Cardiovascular comorbidities and cancer-directed therapies in Hispanic breast cancer patients: a two-center analysis from the Southwestern U.S - Escobar Gil, Tomas; Sherry, Emily; Borja Montes, Oscar Felipe; Millhuff, Alexandra Claire; Hanson, Valeria Guadalupe; Ayodele, Victoria; Baig, Aymen; Nemunaitis, Jacklyn Marie; Mazo Canola, Marcela (Frontiers in Oncology, 2025)
BackgroundCardiovascular disease (CVD) is a leading cause of mortality among breast cancer survivors, particularly affecting Hispanic women due to a high burden of comorbidities and treatment-related toxicities. However, real-world cardiovascular risk and treatment patterns in this population remain under-characterized.MethodsWe conducted a retrospective review of 394 Hispanic patients with stage I–III breast cancer treated with curative intent between 2022 and 2023 at two institutions in the Southwestern U.S. Data included demographics, cancer therapy, cardiovascular comorbidities, and medication use.ResultsThe cohort had a mean age of 59.9 years and a mean BMI of 30.1 kg/m². Cardiovascular comorbidities were present in 57.5% of patients, which appears numerically higher than rates reported in prior breast cancer cohorts (~40%). Hypertension (45.7%) and diabetes (24.3%) also appeared numerically more common than prior national estimates. Among hypertensive patients, 73.9% were receiving antihypertensives, which is numerically lower than previously published rates (~77%). In contrast, 94.2% of patients with hyperlipidemia were on statins, numerically higher than prior reports (~70%). All patients with CVD were receiving aspirin. Chemotherapy was administered to 66% of the cohort, a numerically higher rate than prior Hispanic breast cancer studies (~48%). Anthracycline use (19.2%) aligned with national de-escalation trends.ConclusionHispanic patients with breast cancer in the Southwestern U.S. face a high burden of cardiovascular disease and numerically lower rates of antihypertensive use. These findings support the need for regionally tailored, integrated cardio-oncology approaches.